Prescribing and using self-injectable antiretrovirals: How concordant are physician and patient perspectives? - Horne, Robert (BioMed Central, 2009)
BACKGROUND: The selection of agents for any treatment regimen is in part influenced by physician and patient attitudes. This study investigated attitudinal motivators and barriers to the use of self-injectable antiretroviral agents among physicians and patients and measured the degree of concordance between physician and patient perspectives. METHODS: Attitudes toward prescribing and usage of self-injectable antiretroviral therapy (SIAT) were assessed by structured interview in 2 cohorts sampled from the European Union and the USA: 499 HIV-treating physicians and 603 treatment-experienced HIV-infected patients. Motivators and barriers to prescribing SIAT were identified from statistical analysis of the associations between physicians' ratings of enfuvirtide-based therapy compared to standard oral-based therapy and 2 indicators of enfuvirtide prescribing behavior. Patients' attitudes were assessed by their responses to a written profile of enfuvirtide and their ratings of the likelihood of accepting a treatment offer. RESULTS: Both indicators of SIAT prescribing behavior were predicted by the same pattern of physician beliefs. Nonprescribing was associated with: (1) the belief that offering enfuvirtide would be perceived negatively by patients, leading to treatment refusal and nonadherence; (2) the belief that prescribing enfuvirtide is harder to justify in terms of time/resources; and (3) a lack of confidence in the efficacy and use of enfuvirtide in practice (all p < 0.05). However, physicians' beliefs were not in concordance with patients' views. After reading a profile of enfuvirtide, 76% patients said that they would be moderately or highly likely to accept a treatment offer, although most (72%) had not discussed enfuvirtide with their doctor. Patients' beliefs predicted the likelihood of accepting enfuvirtide. CONCLUSION: Physician and patient beliefs about SIAT influence prescribing behavior and compliance yet may not be concordant, with patients having more positive attitudes towards SIAT than anticipated by physicians.